Mirror Movements in Acquired Neurological Disorders: A Mini-Review - Liu, Ping; Yuan, Yuan; Zhang, Ning; Liu, Xiaoyan; Yu, Lihua; Luo, Benyan (Frontiers in Neurology, 2021)
Mirror movements (MMs) are specifically defined as involuntary movements occurring on one side of homologous muscles when performing unilateral movements with the contralateral limb. MMs have been considered as a kind of soft neurological signs, and the persistence or reappearance of MMs in adults is usually pathologic. In addition to some congenital syndrome, MMs have been also described in age-related neurological diseases including pyramidal system diseases (e.g. stroke, amyotrophic lateral sclerosis) and extra-pyramidal disorders (e.g. Parkinson's disease, essential tremor). With the advances in instrumentation and detection means, subtle or subclinical MMs have been deeply studied. Furthermore, the underlying mechanism is also being further elucidated. In this mini-review, we firstly discuss the MMs examination means, and then review the literature regarding MMs in individuals with acquired neurological disorders, in order to further understand the pathogenesis of MMs.